Peranan Koperasi dalam Mempertingkatkan Kepentingan Sosio Ekonomi Anggota-Anggotanya. Satu Kajian Kes ke Atas Koperasi Anggota-Anggota Kerajaan Batu Pahat Berhad - Mahmud, Kadar (2004)
The purpose of this study is to see the progress level of social economic status among members of Koperasi Anggota-Anggota Kerajaan Batu Pahat Berhad. This study wants to find out the correlation between independent variables (social interaction, amount of shares and fees, dividend, frequency of taking loans, amount of loan, members collective fund) with the progress level of social economic status. Samples of 354 were taken from a total of 4,417 co-operative members comprising different departments and different lavels of job categories using simple random sampling. Questionnaires were used as the instrument to obtain data and information. The data collected were tested using descriptive and inferential statistics. The result of the research showed that the respondents agreed that the co-operative has an impact on the progress level of social economic status of the co-operative members through upgrading members/members children education and feeling secure as a cooperative members. The correlation analysis showed that independent variables have significant relationship with the progress level of social economic status.